Analysis of Volatility and Factors Affecting Cryptocurrency Prices: A Case Study of Bitcoin and Ethereum - Hardiyanti, Siti Epa (PT Larva Wijaya Penerbit, 2024)
The volatility of cryptocurrency prices, particularly Bitcoin and Ethereum, has become a major concern for investors and researchers due to high price fluctuations and influencing factors. This study aims to analyze the volatility and factors affecting the prices of Bitcoin and Ethereum. The methods used include descriptive analysis, ARCH and GARCH models, and linear regression to identify the impact of macroeconomic factors, cryptocurrency-specific factors, regulation, and market sentiment on price volatility. The results show that Ethereum has higher volatility compared to Bitcoin, with inflation, interest rates, and market sentiment being significant factors affecting volatility. Cryptocurrency-specific factors, such as mining costs and technological developments, also play an important role. The implications of these findings emphasize the importance of risk management for investors and the need for supportive regulation to create a stable investment environment. This study makes a significant contribution to understanding the dynamics of cryptocurrency price volatility and provides insights for policymakers and technology developers.